POLA KOMUNIKASI ORGANISASI DALAM PENINGKATAN KINERJA PEGAWAI DINAS ENERGI DAN SUMBER DAYA MINERAL PROVINSI SUMATERA UTARA - Syafira Rahma Putri; Nursapia Harahap; Syahrul Abidin (Lafadz Jaya Publisher, 2023)
This research is entitled Organizational Communication Patterns in Improving Employee Performance at the Energy and Mineral Resources Office of North Sumatra Province. The purpose of this study was to determine how organizational communication patterns can improve employee performance at the Energy and Mineral Resources Office of North Sumatra Province. The results showed that (1) The Energy and Mineral Resources Office of North Sumatra Province uses a wheel communication pattern in which the head of the department provides information through oral communication during routine meetings and writing in the form of letters or information submitted in Whatsapp groups consisting of all employees. (2) for the performance of employees is classified as good because the quantity of all employees in completing the task is in accordance with the set target, then the quality of the workers is classified as good even though there are limited human resources, discipline, craftsmanship, and cooperation between employees is classified as good. (3) the communication pattern that can improve employee performance is the Y communication pattern because only the head of the department and the head of the field / section conduct meetings so that other employees can continue to do their respective duties so that the quantity and quality of employee work is maintained and more effective because the information conveyed by the head of the department during the meeting can be conveyed back from the head of the field / section to the employees in the field / section.